Transesterification Of Extracted Spent Bleached Earth (Sbe) Oil For Biodiesel Production Using Alkaline Supported Sbe Heterogenous Catalyst - Keasavan, Thivya (2024)
Proper disposal of spent bleaching earth (SBE) is much anticipated to create a circular economy. In this study, a two-pronged approach was employed to utilize SBE from palm oil refinery for its suitability to act as second-generation biofuel feedstock and catalyst.